2018
DOI: 10.1021/acsnano.7b08969
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Binding Amyloid Fibrils Self-Assemble into Reversible Hydrogels with Antibacterial Activity

Abstract: Adaptable hydrogel networks with reversible connectivity have emerged as a promising platform for biomedical applications. Synthetic copolymers and low-molecular-weight gelators (LMWG) have been shown to form reversible hydrogels through self-assembly of the molecules driven by self-complementary hydrophobic interaction and hydrogen bonding. Here, inspired by the adhesive proteins secreted by mussels, we found that simply adding natural polyphenols, such as epigallocatechin gallate (EGCG) to amyloid fibrils pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
180
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(183 citation statements)
references
References 69 publications
2
180
0
1
Order By: Relevance
“…[177] The TNA hydrogel exhibits adhesiveness, extensibility, and superior in vivo hemostatic ability. Very recently, Hu et al [178] demonstrated the formation of a hydrogel by adding polyphenols such as EGCG to amyloid fibrils present in the nematic phase. The resulting gels have been observed to be shear thinning and thermostable in the range of 25-90 °C without occurrence of a phase transition.…”
Section: Gelsmentioning
confidence: 99%
“…[177] The TNA hydrogel exhibits adhesiveness, extensibility, and superior in vivo hemostatic ability. Very recently, Hu et al [178] demonstrated the formation of a hydrogel by adding polyphenols such as EGCG to amyloid fibrils present in the nematic phase. The resulting gels have been observed to be shear thinning and thermostable in the range of 25-90 °C without occurrence of a phase transition.…”
Section: Gelsmentioning
confidence: 99%
“…Particularly strong tendency to integrate EGCG into micelles was reported in the case of milk casein 30 . A reversible fibrillar self-assembly of proteins with ability to up-take EGCG was also recently reported 31 . In the present work we focus on fibrillar aggregation of micellar κ-casein, a well-known protein from milk 32 , and investigate how the tannin epigallocatechin-gallate (EGCG, 458 g/mol) can be used to understand the aggregation mechanism and control the system.…”
Section: Introductionmentioning
confidence: 74%
“…For instance, mutations and grafts on the peptide sequence of functional amyloids such as curli can change the interfacial strength, as well as mechanical properties such as bending rigidity, which may explain variations in the performance of amyloid based adhesives. [59][60][61][62] Furthermore, polymeric or DNAbased self-assembled nanofibers could also be studied in a similar manner to examine whether biological amyloids offer any advantages over such systems in terms of adhesive performance. 63,64 The current work focusing on the development of computational phase diagrams for adhesion sets the stage for pursuing these diverse research directions to evaluate a variety of interfacial phenomena relevant to biological, as well as engineered adhesives.…”
Section: Resultsmentioning
confidence: 99%